PostGeoOlap: an Open-Source Tool for Decision Support - Colonese, Giovanni; Manhães, Rodrigo Soares; González, Sahudy Montenegro; de Carvalho, Rogério Atem; Tanaka, Asterio Kiyoshi (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2005: Anais do II Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2005.14976, 2005)
This work describes PostGeoOlap, a decision support tool that integrates OLAP (On-Line Analytical Processing) and GIS (Geographical Information System) technologies in a single application. PostGeoOlap is an open source and a general-purpose tool to be used by application developers to easily develop their decision support applications. This tool works on the PostGreSQL DBMS using its spatial extensions (PostGIS) and performs the analytical and geographical functionalities using data warehouses.